The Effectiveness of Utilizing Song Media in Enhancing Mandarin Language Vocabulary Proficiency Among Students - Darwin, David (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study was conducted to analyze the effectiveness of using song media in developing students' Chinese vocabulary skills. The design used in this research is quasi experimental with the form of non-equivalent control group design. The population in the study were Kinderfield School East Jakarta students. The sample in this study used all members of the population, totaling 35 students, consisting of 19 experimental class students and 16 control class students. The research approach used is quantitative with a Quasi Experiment design, which involves two groups, namely the experimental group and the control group. Data and data sources in this study include data obtained from interviews, field notes, and tests given to students. Data collection techniques were conducted through documentation, structured interviews, and tests consisting of pre-test and post-test. The sampling technique used was non-probability sampling with saturated sampling type. Data analysis techniques were carried out using quantitative experimental techniques, including validity tests, reliability, normality tests, homogeneity tests, and hypothesis testing using the Independent Sample Test with the help of IBM SPSS Statistics version 22 software. The study showed that students in the experimental class experienced a significant improvement in Chinese speaking skills based on the post-test results, and the mean score of the experimental class was higher than the control class, indicating the effectiveness of the teaching method using song media in improving Chinese language skills at Kinderfield School East Jakarta.